Decision Support System for Selecting the Best Facial Wash Brand for Acne-Prone Skin Using the Fuzzy Analytical Hierarchy Process (F-AHP) Method - Armaya, Devira Yuda; Rosnita, Lidya; Asrianda, Asrianda; Rachman, Aulia; Azhari, Muhammad (Journal of Advanced Computer Knowledge and Algorithms, 2025)
Acne is a problem that is often experienced by women. The factors that trigger acne skin problems are due to the pores on the facial skin that are clogged with oil, and the presence of bacteria. This research was conducted to provide a decision support system in recommending brands facial washthe best for acne prone skin types through the value of the intensity of importance of criteria such as price, packaging form, packaging size, active ingredient content, and packaging design. The final result of the calculation process using the method fuzzy AHP produces the lowest to the highest weight value for each brandfacial wash. And the final ranking data shows that there are 5 brand recommendations facial wash with the highest value of the other alternatives. That is there is an alternative code A04 which has the highest value asfacial wash the best for acne prone skin types, namely the brand is The Body Shop Tea Tree Skin Clearing Facial Wash with a total value of 7.663, and followed by alternative code A13 namely is Some By Mi AHA BHA PHA with a total value of 7.663, alternative code A07 is Miracle Cleansing with a total value of 7.337, the alternative code A15 is Ponds Anti Bacterial Facal Foam with a total value of 7.326, and the last alternative code A14 is Emina MS Pimple Acne Solutonwith a total score of 6.663.